2022
DOI: 10.1155/2022/8069152
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Exerts Beneficial Effect on Testicular Ischemia-Reperfusion Injury in Rats

Abstract: Testicular torsion-detorsion results in testicular ischemia-reperfusion injury, which is associated with overgeneration of reactive oxygen species. Salidroside, a major bioactive ingredient extracted from Rhodiola rosea, has strong antioxidant activity. The purpose of this study was to examine the effect of salidroside on testicular ischemia-reperfusion injury. Sixty rats were randomly separated into 3 experimental groups: group A = sham-operated control; group B = testicular ischemia-reperfusion; and group C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…28 Aerobic organisms have developed a robust antioxidant defense mechanism to protect against ROS-induced cellular damage. 27 In present study showed that significantly higher MDA concentration and significantly lower SOD protein expression in kidney tissue were observed in the LPS group compared with the control group (Figure 3). These findings suggest that excessive ROS during kidney injury depletes these antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…28 Aerobic organisms have developed a robust antioxidant defense mechanism to protect against ROS-induced cellular damage. 27 In present study showed that significantly higher MDA concentration and significantly lower SOD protein expression in kidney tissue were observed in the LPS group compared with the control group (Figure 3). These findings suggest that excessive ROS during kidney injury depletes these antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 50%
“…However, excessive amounts of ROS produced during pathological conditions. 27 High levels of ROS can destroy cellular macromolecules, including proteins, lipids, and nucleic acids resulting in cellular damage. 28 Aerobic organisms have developed a robust antioxidant defense mechanism to protect against ROS-induced cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…In order to counteract I/R effects, numerous therapeutic approaches acting on the different pathways have been tried, either with natural substances [ 25 , 26 , 27 ] or with nutraceuticals [ 28 , 29 , 30 ]. Among them, selenium (Se), a trace element able to lower oxidative stress [ 31 , 32 ], reduced MDA levels and increased superoxide dismutase (SOD) activity and ameliorated structural damages after testicular experimental I/R [ 33 ].…”
Section: Introductionmentioning
confidence: 99%